Development of a Novel Oral Vaccine Against Human Resipratory Syncytial Virus - Jalilian, Farid Azizi (2011)
Human respiratory syncytial virus (HRSV) is the leading cause of bronchiolitis and pneumonia in infants, children, the elderly and the immune-compromised. The goal of immunization is to provide sufficient protection to prevent serious lower respiratory tract diseases leading to hospitalization and reducing the frequency of complications such as otitis media. Prevention and treatment of HRSV infection using antiviral agents is challenging because it is a rapid acute infection and by the time the infection is recognized it may be too late to control the disease with any antiviral therapy alone. Thus, there is a worldwide need for an HRSV vaccine. Studies have shown that the immunogenic domains of F and G proteins could confer protection against HRSV infection in vaccinated hosts. In the present study, firstly the immunogenic domain of HRSV G domain was expressed in Escherichia coli . Then a rabbit was immunized using purified-recombinant G domain protein. The results of neutralization assay showed that G domain alone could raise active polyclonal antibodies against HRSV successfully. Secondly, the potential of G and F immunogenic domains as vaccine candidates were studied by using live bacterial vaccines. Both the G and F domains were separately initially cloned in pKMSInak plasmid before they were surface displayed on Salmonella typhi Ty21a used as the delivery system. The surface displayed G and F domains were detected using indirect immunofluorescence, sero-agglutination and outer membrane protein separation approaches suggesting that the Inak protein successfully carried the G and F domains to the surface of Salmonella cells. For in vivo evaluation of the designed vaccines, Balb/c mice were immunized orally with live Salmonella cells harboring pKMSInak-G or pKMSInak-F and challenged against HRSV. The humoral (TH2), cellular (TH1) and mucosal immune (IgA) responses of the immunized mice were studied by measuring cytokines (IL-2, IL-4, IL-5, IL-9, IL-10, IL-12, IL-13, IL-17, IFN-γ and TNF-α), chemokines (RANTES and MIP-α) and immunoglobulins (IgG, IgG1, IgG2a, IgG2b and IgA) levels in their sera before and after challenging with HRSV. Lymphocyte proliferation assay was performed to evaluate the cell mediated immunity. Histopathological examinations were also carried out as confirmatory tests. The results showed that pKMSInak-G and pKMSInak-F vaccines could significantly enhance TH1 and TH2 responses as well as mucosal immunity in the immunized mice compared to the control group. Histopathological examinations indicated that the immunized mice had significantly lesser lung tissue damage than the control. Moreover, the obtained ratios of TH1/TH2 were desirable (~1) suggesting that Salmonella cells carrying pKMSInak-G and pKMSInak-F are potent vaccine candidates against HRSV.